2008
DOI: 10.3357/asem.2235.2008
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Nervous Function During Whole-Body Cold Exposure Before and After Cold Acclimation

Abstract: Cold exposure increased sympathetic activity, which was blunted after cold acclimation. Parasympathetic activity showed a minor increase in cold, which was enhanced after cold acclimation. In conclusion, cold habituation lowers sympathetic activation and causes a shift toward increased parasympathetic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
65
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 26 publications
9
65
0
1
Order By: Relevance
“…These authors reported that the increases in BP and heart rate during isometric HG were not different in warm (25°C) and cold (10°C) ambient environmental conditions (32). The results of the present investigation are similar, as the increases in BP during HG were not different during combined cold stress in young adults.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…These authors reported that the increases in BP and heart rate during isometric HG were not different in warm (25°C) and cold (10°C) ambient environmental conditions (32). The results of the present investigation are similar, as the increases in BP during HG were not different during combined cold stress in young adults.…”
Section: Discussionsupporting
confidence: 80%
“…To our knowledge, only one previous study has examined cardiovascular function during combined isometric exercise and whole body cold exposure in young adults (32). These authors reported that the increases in BP and heart rate during isometric HG were not different in warm (25°C) and cold (10°C) ambient environmental conditions (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, although the effect on PRV of cooling varies with the duration of the temperature change, it is thought that cold exposure modulates short-term variability (i.e., HF, RMSSD, and SD1) more than long-term variability (LF, SDNN, and SD2). 8 This indicates that cold exposure modulates SNS-PSNS balance by causing a shift toward increased PSNS activity. Previous studies comparing PRV derived from PPG and ECG under optimal rest conditions did not report significant differences in PRV assessment.…”
Section: Sympathetic and Parasympathetic Autonomous Nervous System Comentioning
confidence: 99%
“…[5][6][7] Under resting conditions, recordings derived from PPG and ECG demonstrate a high degree of correlation (∼r > 0.93). 7,8 However, PRV PPG also has disadvantages. While sufficient accuracy can be obtained when subjects are under optimal resting conditions, PRV PPG has been reported to be vulnerable to motion artifacts, 6 physical exercise, 5 or mental stressors, 7 making it considerably less accurate compared to ECG.…”
Section: Introductionmentioning
confidence: 99%